Conflicting Normative Systems and Institutional Challenges to Human Rights in Africa: A Case Study in Zambia - Chikoye, Mwaka Daniel (Eastern Mediterranean University - Doğu Akdeniz Üniversitesi, 2021)
African states are faced with critical human rights challenges which continue to imperil the lives of countless citizens on the continent. Political instability, wars, genocide, and poverty to name a few have all played significant roles in aiding the violation of basic rights which presently affect the liberties of Africans. Zambia specifically, have displayed poor records in various aspects of human rights such as labor rights, women’s rights, refugees, and the rights of internally displaced persons (IDPs) consequently gaining attention globally. To realize the extent of the African human rights conundrum, it is important to point out the most basic underlying causal factors of abuse of human rights. In which two key factors account for the poor human rights record in Zambia; Institutional challenges, and socio-cultural influences on continent-wide value systems which continues to struggle to accommodate the universal human rights model enshrined in the Universal Declaration of Human Rights (UDHR). The African Charter on Human and Peoples’ Rights, with its emphasis on group rights and individual duties challenges the Universal account of rights. The cultural differences presented not only the tension between individual and group rights but also the question as to whether the universalism of human rights is possible. The focus of this thesis are the challenges facing human rights on the African continent today. It provides a short historical backdrop before moving on to an examination of the normative framework that presently prevails at the continental level. Incorporated are issues such as cultural relativism or reductionism, the iv structure and content of the African Charter on Human and Peoples' Rights, the human rights of women. Findings present various reasons such as: poverty, spirituality, lack of education and the government of Zambia continue to play a role in hindering the possibility of wide acceptance of universalism of human rights in Zambia. Keywords: human rights, universalism, cultural relativism, UDHR, ACHPR, institutional challenges, social cultural Influences.

ÖZ:Afrika devletleri, kıtadaki sayısız vatandaşın hayatını tehlikeye atmaya devam eden kritik insan hakları sorunları ile karşı karşıyadır. Siyasi istikrarsızlık, savaşlar, soykırım ve yoksulluğun tümü, şu anda Afrikalıların özgürlüklerini etkileyen temel hakların ihlaline yardım etmede önemli roller oynamıştır. Zambiya, özellikle işçi hakları, kadın hakları, mülteciler ve ülke içinde yerinden edilmiş kişilerin (ÜİYOK'ler) hakları gibi insan haklarının çeşitli yönlerinde zayıf kayıtlar sergilemiş ve sonuç olarak küresel olarak dikkat çekmiştir. Afrika insan hakları muammasının kapsamını anlamak için, insan haklarının kötüye kullanılmasının altında yatan en temel nedensel faktörlere işaret etmek önemlidir. Zambiya'daki zayıf insan hakları sicilinin iki temel faktörden kaynaklandığı; İnsan Hakları Evrensel Beyannamesi'nde (UDHR) yer alan evrensel insan hakları modeline uyum sağlamak için mücadele etmeye devam eden kıta çapında değer sistemleri üzerindeki kurumsal zorluklar ve sosyo-kültürel etkiler. Grup haklarına ve bireysel görevlere vurgu yapan Afrika İnsan ve Halkların Hakları Şartı, Evrensel haklar hesabına meydan okuyor. Kültürel farklılıklar, sadece bireysel ve grup hakları arasındaki gerilimi değil, aynı zamanda insan haklarının evrenselciliğinin mümkün olup olmadığı sorusunu da ortaya koydu. Bu tezin odak noktası, bugün Afrika kıtasında insan haklarının karşı karşıya olduğu zorluklardır. Şu anda kıta seviyesinde hüküm süren normatif çerçevenin incelenmesine geçmeden önce kısa bir tarihsel zemin sağlar. Kültürel görecelik veya indirgemecilik, Afrika İnsan ve Halkların Hakları Şartı'nın yapısı ve içeriği, vi kadınların insan hakları gibi konular dahil edilmiştir. Bulgular, yoksulluk, maneviyat, eğitim eksikliği ve Zambiya hükümeti gibi çeşitli nedenler ortaya koymaktadır ve Zambiya hükümeti, Zambiya'da insan haklarının evrenselciliğinin geniş çapta kabul edilmesi olasılığını engellemede rol oynamaya devam etmektedir. Anahtar Kelimeler: insan hakları, evrenselcilik, kültürel görecelik, İHEB, ACHPR, kurumsal zorluklar, sosyal kültürel Etkiler.
Master of Arts in International Relations. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2021. Supervisor: Assoc. Prof. Dr. Wojciech Forysinski.
Keywords: Human Rights-Civil Rights-Zambia-AfricaSubject term:Politics and Government-Zambia; Human rights; universalism; cultural relativism; UDHR; ACHPR; institutional challenges; social cultural Influences